Inquiry of analytical methodologies for measuring two gold cyanide solutions in electronic devices industry in Costa Rica - Pérez-López, Esteban (2017)
This paper is based on investigation and experimentation of two analytical methodologies, in order to determine which one is most reliable for the quantification of gold in cyanide solutions, and thus reduce the variability of the results, due to the method of quantification metal, implemented as quality control in the production process of a company in Costa Rica technological devices.The gold dissolved in cyanide can be used in the chemical plating process to produce a coating on another metal, a process that is widely used in the manufacture of electrical connectors, and which thus can deposit a specific amount of a metal where required for the connector to have a good electrical conduction.Due to the importance of the bath containing gold in the electrodeposition process, it is necessary to have an analytical method that is capable of quantifying the gold in a reliable way, which is why two analytical techniques were studied: atomic absorption spectrophotometry Spectroscopy and X-Ray Fluorescence, to establish what is the most appropriate analytical method for the analysis of gold in cyanide solutions, and then validated to ensure reliability of results. After this study it was found that the analysis of gold by atomic absorption technique provides more accurate results and accuracy, to be established with high reliability by requiring it under laboratory conditions set forth herein.